Silicon and sodium attenuate potassium deficiency in Eruca sativa Mill. - Alves, Deyvielen Maria Ramos [UNESP]; de Mello Prado, Renato [UNESP]; Barreto, Rafael Ferreira (Elsevier, 2024)
Potassium (K) fertilizers are limited and non-renewable. Exploring the use of sodium (Na) and silicon (Si) as alternatives to reduce its use may be an alternative. However, the relationship of these elements with arugula nutrition and quality is unknown. Therefore, the objective of this study is to verify the effects of Na and Si on the parameters of arugula under conditions of K deficiency and sufficiency. The experiment was conducted in a greenhouse in a hydroponics system. The treatments used were K-sufficient, K-sufficient with Na, K-sufficient with Si, K-deficient, K-deficient with Na, and K-deficient with Si. Evaluations of physiological, biochemical, nutritional, and growth aspects were performed. Si supply increased the production of total phenols, ascorbic acid, and carotenoids in K-deficient plants. Both elements attenuated the damage caused by K deficiency and improved quality. This is an innovative strategy for the sustainable cultivation of this species.
Keywords: Arugula; Beneficial element; Chemical element; Plant nutrition